2022
DOI: 10.1515/almed-2022-0065
|View full text |Cite
|
Sign up to set email alerts
|

Control of occult hepatitis B virus infection

Abstract: Background The diagnosis of hepatitis B virus (HBV) infection requires HBV DNA testing and serologic testing for detection of the surface antigen (HBsAg) and the hepatitis B core antibody (anti-HBc). There is a population of patients with occult HBV infection (OBI), which is not detected by HBsAg or HBV DNA quantification in blood, despite the presence of active replication in the liver. Scope This document provides a definit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Using conserved epitopes predicted from global consensus sequences against NS3-4A could offer broader protection against multiple isotypes of the Hepatitis C virus [49]. Given the significant role of viral HBx and HBc proteins in association with cccDNA in promoting HBV replication, achieving a functional HBV cure remains a formidable challenge [50][51][52][53][54][55][56][57][58]. This study paves the way for designing innovative anti-HBV vaccines and therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…Using conserved epitopes predicted from global consensus sequences against NS3-4A could offer broader protection against multiple isotypes of the Hepatitis C virus [49]. Given the significant role of viral HBx and HBc proteins in association with cccDNA in promoting HBV replication, achieving a functional HBV cure remains a formidable challenge [50][51][52][53][54][55][56][57][58]. This study paves the way for designing innovative anti-HBV vaccines and therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo studies have shown that the acetylation status of histones (H3/H4) connected to cccDNA controls HBV transcriptional and replicational activity. While it is plausible that these epigenetic mechanisms contribute to the potent inhibition of viral replication, incredibly low levels of cccDNA in the absence of HBsAg persist in OBI patients 19 …”
Section: Pathogenesis Of Occult Hbv Infectionmentioning
confidence: 99%
“…HBV reactivation is mainly linked to several factors, such as patients with detectable HBV DNA (even with a low viral load) who are negative for anti‐HBs antibodies, 14,19 a history of HBV infection and a history of HBV infection in the family; older age (>65); male gender; and chronic illness. The complexity of HBV reactivation in OBI patients necessitates ongoing research, and there are relationships between variables, including morbidity, etiology, therapy, and prevention.…”
Section: Clinical and Epidemiological Characteristicsmentioning
confidence: 99%